Desempenho eletroquímico dos óxidos mistos LiMnNiO4 e LiNi1/3Mn1/3Co1/3O2 e seus compósitos condutores com polianilina e polipirrol para cátodos de baterias de íon lítio - Freitas, Admildo Costa de (2014)
The present work aims to study the influence of the calcination time on the structure of the mixed oxide. It also aims to achieve the amount of constituent materials that favors the electrochemical properties of the composites LiMnNiO4/polyaniline for application as cathodes in lithium ion batteries. The XRD of the oxides calcined at 800 °C for different calcination periods showed the same diffraction peaks, however, that calcined for 12 h showed the best defined diffraction peaks, which were indexed to the rhombohedral structure. The crystallite size obtained for this oxide was 54.23 nm. Cyclic voltammograms of all composites showed predominantly faradaic profile. However, the LiMnNiO4/polyaniline composite containing 400 mg of LiMnNiO4 showed the highest current density, and consequently, the anodic charge. From the TGA, it was determined that the proportion between the constituent materials in LiMnNiO4 (400 mg)/polyaniline composite was 30% for oxide and 70% for polyaniline. So, this proportion between the constituent materials resulted in an intensification of the electrochemical properties of the composite LiMnNiO4/PAni. Based on these data, the composite LiNi1/3Mn1/3Co1/3O2/PAni were chemically synthesized using 400 mg of oxide. The DRXs of the conducting composites showed that amorphicity of the conducting polymers hid the diffraction peaks characteristic of oxides. The infrared spectra showed that in fact the conductive composites were chemically synthesized. Micrographs of LiNi1/3Mn1/3Co1/3O2 showed a compact morphology with high crystallinity. Already, SEM of the conducting composites showed a predominant characteristic morphology of the conducting polymer, indicating that these conductive polymers homogeneously coated oxides particles. The DTA analysis of the composite revealed that there was not a significant increase in thermal stability when compared with those of their constituent materials. Cyclic voltammograms of LiNi1/3Mn1/3Co1/3O2 (400 mg)/PAni and LiNi1/3Mn1/3Co1/3O2 (600 mg)/Ppy composites had values of current density and consequently the anodic charges higher than those of its constituent materials arising from the synergistic effect between these materials. The values of charge transfer resistance of the composites were lower than those obtained for PAni and the oxides investigated, indicating favoring the electron transfer rate in the composites. The galvanostatic chronopotentiometry tests showed that discharge specific capacities values obtained for LiMnNiO4/PAni and LiNi1/3Mn1/3Co1/3O2/PAni were 112 and 147 mA h g-1 after 20 cycles, respectively. These discharge specific capacities values of the composites remained almost constant during 20 charges and discharge cycles, indicating a good electrochemical stability. Therefore, the conducting composite resulting from the association of mixed oxides (LiNi1/3Mn1/3Co1/3O2 and LiMnNiO4) and polyaniline showed an intensification of their electrochemical properties and thus, are promising materials as cathodes in lithium ion batteries.